Evaluasi Tempat Penyimpanan Sementara Limbah Non B3 Terdaftar Pada PT. X - Karunia, Irma; Praditya S.Ardisty Sitogasa (Universitas Nusa Putra, 2025)
PT X is a manufacturing industry engaged in the Food and Beverage (F&B) sector that produces registered non-B3 waste in the form of Fly Ash and Bottom Ash, Fly Ash and Bottom Ash produced from burning coal in boilers. This industry has a Temporary Storage Place or TPS for Fly Ash and Bottom Ash waste, the evaluation is carried out based on the regulations of Government Regulation no. 22 of 2021 and Ministerial Regulation of Environment and Forestry no. 19 of 2021, The results of the evaluation showed the suitability of non-B3 waste TPS registered with PT. X, however, several times it is overloaded if it follows the ideal amount that has been determined, it occurs due to the unstable transportation vendor and production rhythm. The stages of Evaluation of Temporary Storage Places for non-B3 waste registered with PT X include waste identification, calculation of the capacity of Temporary Storage Sites, adjusting the facilities in the Temporary Storage Place with applicable regulations, analyzing the generation data generated by the boiler per day, from the results can be analyzed what things affect the number of Temporary Storage Places with an ideal capacity of 48 Jumbo Bags